(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The accurate prediction and prevention of earthquakes remains challenging. Consequently, the primary approach to mitigate the impact of earthquakes is through disaster risk reduction efforts. One significant strategy involves conducting seismic vulnerability analyses based on disaster scenarios. This study aims to identify and map areas with varying levels of seismic vulnerability, analyzing the factors contributing to vulnerability in the South Bengkulu Regency. Secondary data, including peak ground acceleration (PGA) values, were collected, along with microtremor data obtained through the Horizontal to Vertical Spectral Ratio (HVSR) method. The recorded microtremor data serve as input parameters for PGA, Modified Mercalli Intensity (MMI), Seismic Vulnerability Index (Kg), shear wave velocity (Vs), and the time-averaged shear wave velocity for the first 30 m depths (Vs30) values. The findings reveal that, overall, seismic vulnerability in the South Bengkulu Regency can be categorized as low. However, specific areas, particularly in the southwestern and northeastern zones, exhibit relatively higher levels of vulnerability. The heightened vulnerability in these areas is attributed to elevated PGA values, despite the region’s generally high soil density, which acts as a mitigating factor against earthquake threats.